Ameliorative effects of Xue-Fu-Zhu-Yu decoction, Tian-Ma-Gou-Teng-Yin and Wen-Dan decoction on myocardial fibrosis in a hypertensive rat mode. Issue 1 (December 2015) - Zhang, Guohua; Yang, Guang; Deng, Yan; Zhao, Xiangling; Yang, Yingbao; Rao, Jinjun; Wang, Wenya; Liu, Xin; He, Jian; Lv, Lin
Abstract Background Xue-Fu-Zhu-Yu decoction (XFZYD), Tian-Ma-Gou-Teng-Yin (TMGTY) and Wen-Dan decoction (WDD) are Chinese herbal formulas used to treat hypertension and cardiovascular diseases in traditional Chinese medicine (TCM). The goal of our study is to determine if XFZYD, TMGTY or WDD treatment ameliorated myocardial fibrosis in spontaneously hypertensive rats (SHRs) and to identify the mechanisms underlying any beneficial effects observed during the courses of the investigation. Methods Forty-five 12-week-old male spontaneously hypertensive rats and five age-matched male Wistar-Kyoto control rats were studied for 16 weeks. Each day 6 g∙kg−1 or 12 g∙kg−1 of XFZYD, TMGTY or WDD was orally administered at the indicated dose, and the systolic blood pressure (SBP) of all rats was measured using the tail-cuff method. Collagen levels were measured via hydroxyproline content assays and histological examination. Transforming growth factor beta-1 (TGF-β1 ) protein levels were determined via immunhistochemical and Western blot analysis. TGF-β1 mRNA levels were assessed using real-time reverse transcription polymerase chain reaction. Results Systolic blood pressure was unaffected, but collagen and TGF-β1 levels in SHRs treated with captopril and XFZYD (12 g∙kg−1 ) were significantly reduced when compared with untreated control SHRs. Administration of 12 g∙kg−1 XFZYD increased myocardial cell protection and decreased TGF-β1 mRNA and protein expression when compared with the other SHR treatment groups. Conclusions XFZYD treatment demonstrated a superior ability to reverse myocardial fibrosis when compared with WDD or TMGTY treatment in SHRs. XFZYD also decreased TGF-β1 mRNA and protein expression, suggesting that the TGF-β1 signaling pathway plays a role in the therapeutic effects of XFZYD treatment.